Influence of Aging Temperature on the Electrochemical Corrosion Behavior of an Age-Hardening 7xxx Aluminum Alloy - Boqian Cai; Xiaolong Liu; Yang Yi; Hongyang Li; Fanian Shi (Crystals)
In this paper, the microstructure changes of an Al–6.8Zn–2Mg–2Cu–0.1Zr–0.2Sc alloy for shipbuilding under different T6 states were investigated. The effect of aging temperature on the electrochemical corrosion behavior of the alloy was analyzed by means of SEM, EDS, and TEM, and the corrosion mechanism was revealed. The results show that the bean-shaped Al3(Sc, Zr) phase is formed in the T6 alloy. The matrix-precipitated phase is mainly the GP zone at 120 °C. At 150 °C, part of the GP zone is transformed into the η′ phase, and at 180 °C, it is mainly η′ phase + η phase. After electrochemical testing in a 3.5 wt.% NaCl solution, it was found that the Cu content in the grain boundary η phase increased with the increase in aging temperature, the potential near the grain boundary increased, and the corrosion resistance increased. At the same time, the grain boundary precipitates were coarsened and distributed intermittently, which hindered the formation of corrosion channels and improved the corrosion resistance of the alloy. The corrosion mechanism of the alloy after aging at 120 °C/150 °C was mainly intergranular corrosion and pitting corrosion, while the corrosion mechanism after aging at 180 °C was mainly pitting corrosion.